Narradores de Morro Grande - Sangão / SC: memória, identidade e hibridismo cultural - Tiburcio, Suzana Luiz (2012)
This dissertation presents a study on cultural hybridity. Started from the assumption that identity is constructed through language and is also part of history. It is known that the identities, even distinct, peculiar, interpenetrate, and they may be known according to the situation. As cultural subjects peculiarities such as the ethnic, social, individual, political, cultural legacy are perceived. So narratives taken from interviews with people from one location could reflect elements of the history of that place and aspects of cultural identities. Our goal therefore is to analyze how hybridity may appear in the statements of residents with different ancestries through the narratives obtained through interviews. Specifically, we intend to: a) discuss the concepts of cultural identity, aspects that signal the cultural hybridity, in order to assess the role of language, ethnic legacy and history, b) think of the narrative as a means of expressing cultural identities; c) develop field research, using the technique of oral history, with residents of the city of Sangão -SC, in order to record narratives about events of that place; d) gather and record the narratives of the film Narradores de Javé analyzing the exemplifications of Yahweh and methodologies used in film about the historiographical construction; e) develop analysis verifying the occurrence of cultural hybridity in the interviews / narratives with the selected group. To this end, we selected the research field five (5) Morro Grande neighborhood residents, city of Sangão, SC. In the collection of interviews / narratives was used as the methodological approach, the guidelines of oral history as well as examples from the movie Narradores de Javé. After watching the film it was verified that in its context there were elements which were intended to be investigated, thus justifying his election also as “methodological approach”. We understand the importance of this study in as much as, and as to understand, in the science of language and in the process this study allows the community recover their history. It is considered in this research to study the language and culture, their specificities, contexts, undertake relevant results and also give rise to other research